Wayset-based guidance of multirotor aerial vehicles using robust tube-based model predictive control. (September 2022) - Santos, Davi A.; Lagoa, Constantino M.
Abstract: The present paper is concerned with the wayset-based guidance of underactuated multirotor aerial vehicles (MAVs). A hierarchical guidance and control structure is first established, in which the guidance is realized as a supervisory loop. The lower-level stabilizing attitude and position control laws are assumed to be available. On the other hand, the outer-loop guidance is designed based on a fixed-horizon tube-based robust model predictive control (MPC), which conducts the MAV to visit a given sequence of waysets, without violating their state and control bounds, and allowing the vehicle to rest in each wayset for a specified period. The MPC is designed using a reduced-order closed-loop dynamic model describing the vehicle's translation, which is derived considering the stabilizing position and attitude control laws and the assumption of a time-scale separation between the closed-loop translational and rotational dynamics. This model is put into a discrete-time linear state–space representation subject to additive bounded random disturbance and measurement noise. The properties of the proposed method, which includes the MPC recursive feasibility and robust stability as well as the overall guidance feasibility, are analytically studied. The method is also numerically evaluated using a realistic quadrotor dynamic model, showing its effectiveness and confirming its properties. Highlights: Wayset-based supervisory guidance loop for underactuated multirotor aerial vehicles. Wayset transitions based on dual-mode tube-based robust model predictive control. Proof of recursive feasibility, robust stability, and overall guidance resolvability. Obtained performance and low computational burden encourage real-time implementation.